Estudo sobre características da abordagem STEAM como possíveis indicadores de altas habilidades/superdotação na área de ciências da natureza - Mateus, Ana Carolina Rodrigues (2024)
This dissertation investigates the potential of the STEAM approach (Science, Technology, Engineering, Arts and Mathematics) as a pedagogical strategy for surveying students with possible indicators of High Abilities/Giftedness (AH/SD) in the area of Natural Sciences. Faced with the challenges of inclusive education, especially in the teaching of Natural Sciences, there is a need for strategies that promote active and integrated learning, respecting the potential of each student. The research problem that guided the study was: "How can teachers identify the potential of students with AH/SD indicators in teaching Natural Sciences, through the STEAM approach?" Based on this question, the objective of the study was to analyze the characteristics of the STEAM approach present in the development of solutions for investigative challenges, aiming to survey students with possible indicators of AH/SD in the area of Natural Sciences. The participatory research methodology adopted included the implementation of a practical investigative challenge, developed based on the principles of STEAM, in which a student was encouraged to build a prototype aimed at solving a real problem of a visually impaired person giving medication to the your son. Using a video capture, called "record of the practical investigative challenge," the student documented the steps of creating and explaining the prototype, highlighting the thought process and skills applied. Data analysis focused on identifying manifestations of cognitive and metacognitive skills, STEAM approach and problem-solving ability. In addition, creativity, above-average ability and involvement with the task, essential aspects for the profile of a student with AH/SD, according to Renzulli's Three Rings model. The results revealed that the STEAM approach, combined with investigative teaching, can contribute to the identification of students with high potential, by offering an environment that values innovation, critical thinking and the practical application of scientific knowledge. The student demonstrated interest and involvement with the task, as well as a significant ability to apply theoretical concepts in practice. As a contribution, the study reinforces the importance of pedagogical practices that not only recognize, but also develop the potential of students with AH/SD indicators in Natural Sciences. The STEAM approach is, therefore, recommended as a survey tool and as a means of school enrichment, promoting the comprehensive training of students with high potential. The conclusion points to the need for new research that deepens the use of STEAM in varied contexts and for different student profiles, highlighting the value of inclusive, critical Natural Sciences teaching that values the diversity of talents in the classroom.